Modulation of firing and synaptic transmission of serotonergic neurons by intrinsic G protein-coupled receptors and ion channels - Maejima, Takashi; Masseck, Olivia A.; Mark, Melanie D.; Herlitze, Stefan (Frontiers in Integrative Neuroscience, 2013)
Serotonergic neurons project to virtually all regions of the central nervous system and are consequently involved in many critical physiological functions such as mood, sexual behavior, feeding, sleep/wake cycle, memory, cognition, blood pressure regulation, breathing, and reproductive success. Therefore, serotonin release and serotonergic neuronal activity have to be precisely controlled and modulated by interacting brain circuits to adapt to specific emotional and environmental states. We will review the current knowledge about G protein-coupled receptors and ion channels involved in the regulation of serotonergic system, how their regulation is modulating the intrinsic activity of serotonergic neurons and its transmitter release and will discuss the latest methods for controlling the modulation of serotonin release and intracellular signaling in serotonergic neurons in vitro and in vivo.